2014
DOI: 10.1519/jsc.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Factors Associated With Time to Complete a Change of Direction Cutting Maneuver

Abstract: Cutting ability is an important aspect of many team sports, however, the biomechanical determinants of cutting performance are not well understood. This study aimed to address this issue by identifying the kinetic and kinematic factors correlated with the time to complete a cutting maneuver. In addition, an analysis of the test-retest reliability of all biomechanical measures was performed. Fifteen (n = 15) elite multidirectional sports players (Gaelic hurling) were recruited, and a 3-dimensional motion captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
144
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(160 citation statements)
references
References 22 publications
13
144
1
2
Order By: Relevance
“…Intuitively, it would seem likely that athletes exhibiting greater vertical stiffness during the drop jump would exhibit great leg stiffness during a change of direction. Indeed, the current study reports that faster athletes displayed shorter ground contact times than slower performers, in line with the results of previous investigations (Marshall et al, 2014;Sasaki, Nagano, Kaneko, Takakuni, & Fukubayashi, 2011), and is likely to be indicative of greater leg stiffness during the change of direction. Future research should seek to directly examine leg stiffness during changes of direction in order to better explore the relationship between stiffness and CODS, the absence of a three-dimensional motion capture system precluded such measurements to be used in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Intuitively, it would seem likely that athletes exhibiting greater vertical stiffness during the drop jump would exhibit great leg stiffness during a change of direction. Indeed, the current study reports that faster athletes displayed shorter ground contact times than slower performers, in line with the results of previous investigations (Marshall et al, 2014;Sasaki, Nagano, Kaneko, Takakuni, & Fukubayashi, 2011), and is likely to be indicative of greater leg stiffness during the change of direction. Future research should seek to directly examine leg stiffness during changes of direction in order to better explore the relationship between stiffness and CODS, the absence of a three-dimensional motion capture system precluded such measurements to be used in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Marshall et al (2014) also observed a significant correlation plantar flexor moment at the ankle (R = -0.65) and ankle power (R = -0.77) with the time to complete a lateral cutting task. These results suggest that stiffness around the ankle may contribute to CODS although this was not examined directly in either investigation.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Performance measures that include actual cutting time, however, seem promising, as cutting functionally relates to pelvic lateral tilt range and lateral thorax rotation. 54 In addition, cutting-time testing is reliable and possible in most clinical settings. 54 More research is, however, needed prior to suggesting the widespread, standard clinical implementation of performance-related tests for athletes with groin pain that is not hip related.…”
Section: Function and Physical Performancementioning
confidence: 99%